Acute interstitial nephritis in the south of Iran; an observational study - Khodamoradi, Zohre (J Nephropathol, 2017)
BACKGROUND: Acute interstitial nephritis (AIN) is an emerging cause of acute kidney injury (AKI) during the recent years. OBJECTIVES: There is no data about prevalence, causes, clinical manifestation and outcomes of AIN in our region. Hence, in this study we aimed to find the prevalence of AIN and describe the causes, clinical presentation, and the outcome of AIN in the native kidney biopsies. PATIENTS AND METHODS: We reviewed 934 native kidney biopsies from 2006 to 2014 and collected the data of patients with the diagnosis of AIN including medical history, clinical findings, para-clinical data, pathologic findings, treatment and outcomes. RESULTS: Prevalence of AIN in our center during 2006 to 2014 was 2.5% of all renal biopsies. The common cause of AIN in our study was drugs. Of those patients admitted to hospital due to AIN, 17 patients (70.8%) received corticosteroid, five of them (29.4%) received pulse of corticosteroid, and 12 patients (70.6%) received oral drug. Around, 54.2% of the patients had hemodialysis during admission. Eight patients had received both dialysis and corticosteroid. Two of them (8.3%) remained on dialysis and 8 (33.3%) developed chronic kidney disease, but 14 (58.3%) patients recovered. CONCLUSIONS: The prevalence of AIN in our study is comparable to other studies and we found the great impact of medications on development of AIN.